Die Herausforderung der Moderne. Überleben angesichts der monetären Formalisierung der Beziehungen - Gallo Lassere, Davide (Simmel Studies, 2016)
This paper expands on Simmel’s answer to the increasing depletion of social relationships due to the by then more than an increasingly pervasive monetary economy. Definitively abandoned all hope for a change in the arrangements that structure the social order and dismissed any prospect for a strong opposition, the simmelian’s individual can only aspire to a decent adaptation to the world as it is, trying to protect her intimate personality and to cultivate spaces and moments in which more specifically human features and qualities can flourish.